A Cucuteni-Vădastra Type Dagger from Site 26 at Strzyżów (S-E Poland) Attests to the Intercultural Landscape of the Eneolithic Eastern Carpathians - Zakościelna, Anna; Adamczak, Kamil; Garbacz-Klempka, Aldona; Kowalski, Łukasz (the Authors, 2023)
In the mid-1990s, a copper dagger of the Cucuteni-Vădastra type was found in the Lublin-Volhynian culture cemetery at Strzyżów, south-eastern Poland. The dagger was customized as a pendant and deposited in an inhumation burial that contained the remains of an adult male and over ten other grave offerings dating to the 2nd quarter of the 4th millennium BC. This paper presents the results of archaeological and metallographic examinations of the dagger from Strzyżów and relates them to a wider cultural context of the region. The results of our study show that the dagger has no signs of use-wear, and furthermore indicate that the metal used for its production is fahlore copper which could have been sourced from the Slovak Ore Mountains. The two other Cucuteni-Vădastra type daggers that were discovered in the vicinity of Strzyżów mark the Western Volhynian Upland as a distinct cluster of the Cucuteni-Vădastra dagger industry in Europe. Furthermore, the daggers from Poland evidence a close relationship between the Lublin-Volhynian culture and the Cucuteni-Tripillia complex and attest to the intercultural landscape of the Eastern Carpathians region during the Eneolithic
Keywords: Eneolithic; Lublin-Volhynian culture; grave goods; copper dagger; ED XRF analysis; Western Volhynian Upland